Clinical Impact of Pathogenic Germline Variants in Pancreatic Cancer: Results From a Multicenter, Prospective, Universal Genetic Testing Study. Issue 10 (8th October 2021) - Uson, Pedro L. S.; Samadder, N. Jewel; Riegert-Johnson, Douglas; Boardman, Lisa; Borad, Mitesh J.; Ahn, Daniel; Sonbol, Mohamad B.; Faigel, Douglas O.; Fukami, Norio; Pannala, Rahul; Kunze, Katie; Golafshar, Michael; et al.
Abstract : INTRODUCTION: To report the prevalence and outcomes of unselected pancreatic cancer (PC) patients with pathogenic/likely pathogenic germline variants (PGVs) detected using a universal testing approach. METHODS: We undertook a prospective, multisite study of germline sequencing using a >80 gene next-generation sequencing platform among 250 patients with PC (not selected for age or family history of cancer) between April 1, 2018, and March 31, 2020. Demographic, tumor characteristics, and clinical outcomes were compared between PGV carriers and noncarriers. RESULTS: Of 250 patients, the mean age was 65 years (SD 8.7), 56% was male, 83.6% was White, and 65.6% had advanced disease (stages III and IV). PGVs were found in 15.2% (N = 38) of patients, and 2 patients had more than 1 PGV. Variants of uncertain significance were found in 44.4% (N = 111). Family history of cancer (odds ratio: 2.36, 95% confidence interval: 1.14–5.19, P = 0.025) was associated with a higher risk of PGV. In a median follow-up of 16.5 months, the median overall survival was 16.8 months in PGV carriers compared with 16.5 months in noncarriers (hazard ratio: 0.51, 95% confidence interval: 0.25–1.01, P = 0.05). Higher levels of carbohydrate antigen 19-9 and advanced disease stages (III and IV) were associated with worse outcomes in both groups. Overall, 68% of PGV carriers had mutations in homologous recombination repair genes, including BRCA1, BRCA2, PALB2, ATM, CHEK2, NBN, and RAD51C . DISCUSSION: Universal multigene panel testing in PC reveals that 1 in 6 patients are carriers of PGV. Multigene germline testing should be used to aid in treatment selection, prognostication, and familial cancer counseling.